Novel Thermoelectric Materials and Device Design Concepts - Skipidarov, Sergey; Nikitin, Mikhail; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents and facilitates the interchange of new research and development results concerned with hot topics in thermoelectric generators (TEGs) research, development and production. Topics include prospective thermoelectric materials for manufacturing TEGs operating in low-, mid-, and high temperature ranges, thermal and mechanical degradation issues in prospective thermoelectric materials and TEG modules, theoretical study of novel inorganic and organic thermoelectric materials, novel methods and apparatus for measuring performance of thermoelectric materials and TEGs, and thermoelectric power generators simulation, modeling, design and practice.This book helps researchers tackle the challenges that still remain in creating cheap and effective TEGs and presents the latest trends and technologies in development and production of advanced thermoelectric generation devices. Provides a concentration of new research and development in the field of Thermoelectric energy generation; Facilitates the rapid interchange of new ideas and results to react effectively to the challenges of Thermoelectric generators; Explains both the advancements and challenges in TEGs.
Chapter1: Investigating the performance of Bismuth-Antimony Telluride -- Chapter2: SnSe: breakthrough or not breakthrough? -- Chapter3: Tin Sulfide: a new nontoxic earth-abundant thermoelectric material -- Chapter4: SnTe thermoelectrics -- Chapter5: Lead chalcogenide thermoelectric materials -- Chapter6: High thermoelectric performance in nano-precipitated PbTe-PbSe-PbS quaternary system -- Chapter7: Multicomponent chalcogenides with diamond-like structure as thermoelectrics -- Chapter8: 1-2-2 layered Zintl phases thermoelectric materials -- Chapter9: Skutterudites: breakthrough or not breakthrough -- Chapter10: Half-Heusler thermoelectrics -- Chapter11: Polymer-derived ceramics (PDCs) - a novel inorganic thermoelectric material system -- Chapter12: Grain-boundary engineering for thermal conductivity reduction in bulk nanostructured thermoelectric materials -- Chapter13: Novel measurements and analysis for thermoelectric devices -- Chapter14: Thermoelectric module simulation for radiant heat recovery.
Keywords: Materials; Catalysis; Force and energy; Renewable energy sources; Electric power production; Energy storage; Materials for Energy and Catalysis; Renewable Energy; Electrical Power Engineering; Mechanical Power Engineering; Mechanical and Thermal Energy Storage